The Arroyo Rojo volcanic-hosted massive sulphide deposit (Tierra del Fuego, southernmost Argentina): geology, mineralogy, petrography and mineral chemistry - Biel, Cecilia (2010)
The Arroyo Rojo deposit is the most important polymetallic, volcanic–hosted massive sulphide close to the town of Ushuaia in the rhyolitic belt of the Andes of the Tierra del Fuego. The deposit occurs in a region with north–verging thrusts and folds, within a Late Jurassic regional volcano–sedimentary complex (Lemaire Formation) and near the contact with overlying turbidites of the Yahgán Formation. This deposit covers rhyolite and dacite and is overlain by a complex unit composed by felsic tuff, ignimibrite and flows. The massive sulphide lens exposure is traced for over 250 m along its strike and varies from 1.5 to 4 m in thickness. Deformation is evident by a pinch–and–swell structure which splits the ore body into two portions: a pyrite–rich zone at the base that passes upwards to massive ore, and a laminated upper portion. Ore minerals include pyrite, sphalerite, chalcopyrite, galena and minor tetrahedrite and bournonite. Neither barite nor Fe oxides or chert are found within or above the massive sulphide lens. Drilling exploration indicated ore interceptions at depth with a true thickness between 3 and 18.6 m of 1% Cu, 1.4% Pb and 3% Zn. In spite of the deformation relative to a shear zone, massive sulphide ore of the Arroyo Rojo deposit retains many undeformed textures as framboids, polyframboids and banding, among others, suggesting early crystallization history. In addition, deformation, recrystallization and annealing textures are also identified. Footwall and hanging–wall felsic volcanic rocks are altered to chlorite–sericite–pyrite–quartz assemblages, being the hydrothermal alteration strongest below the orebody, where it exhibits a roughly concentric zonation with a silicic and chloritic inner zone and a sericitic external zone. Chlorite and mica compositions show systematic changes with distance from ore: from Mg–rich chlorite and phengite in proximal zones to Fe–rich chlorite and phengitic muscovite in distal areas. In spite of previous works that classify the Arroyo Rojo deposit under the Kuroko type, that is, ore deposition from buoyant fluids forming mounds, the geological and mineralogical evidence points to a sulphide deposition in a brine pool.